Effect of Corporate Attributes on Sustainability Reporting of Listed Non-financial Firms in Nigeria - Razaq, Abubakar Garba; Alhassan, Abdulkarim; Ame, Jacob (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
The conventional accounting practice is predicated on the protection of overriding interests of wealthy capital providers. This is clearly demonstrated in the contents of general-purpose financial statements, which serves as a bastion of accountability and stewardship. This study examined the effect of corporate attributes on sustainability reporting of listed non-financial firms in Nigeria. The study measured corporate attributes with firms’ attributes (firm size, profitability, leverage, liquidity), board attributes (board size, board independence, board gender diversity, board financial expertise) and ownership attributes (foreign, managerial, institutional, ownership concentration) and sustainability reporting measured by sustainability disclosures in line with Global Reporting Initiative (GRI) standards. The study adopted ex-post facto research design relying on secondary data obtained from annual reports of the population, which comprised of 116 non-financial firms listed on the Nigeria Exchange Group (NGX) as at 31st December 2020 with sample size of 51 firms, covering the period of 2011 – 2020. The study employed the use of multiple regression panel model to analyze the data using E-view 10 statistical tool. According to the results of random effect regression, profitability, liquidity, leverage, institutional ownership, firm size, foreign ownership, board size and board financial expertise have positive and significant effect on sustainability reporting. Based on the findings, the study concluded that corporate attributes can effectively enhance the sustainability reporting of firms. Thus, the study recommended among others that regulators in financial reporting should monitor corporate attributes in firms closely as a measure of enhancing sustainability reporting of listed non-financial firms in Nigeria.